Optimization and Flow Characteristics in Advanced Fluid Machinery - Wang, Chuan; Cheng, Li; Si, Qiaorui; Hu, Bo (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Advanced fluid machinery is the key component in the sustainable development of energy and water resources, including various transport processes for liquids. Where fluid flows, fluid machinery works. Therefore, fluid machinery occupies an important position in the social economy. This Special Issue, entitled "Optimization and Flow Characteristics in Advanced Fluid Machinery", provides a platform for the sharing of knowledge among researchers in the field of fluid machinery, and includes theoretical analyses, numerical simulations, and experimental studies. This Special Issue covers a wide range of disciplines as follows: (1) optimization of advanced fluid machinery using different advanced algorithms; (2) flow characteristics of advanced fluid machinery using numerical and experimental methods; (3) vibration and noise of advanced fluid machinery; (4) fluid-structural coupling analysis of advanced fluid machinery; (5) cavitation and multi-phase flow of advanced fluid machinery; (6) simulation and optimization of new energy systems; and (6) other aspects of fluid machinery.This Special Issue contains 27 manuscripts, including 1 Editorial and 26 scientific articles. We would like to thank all of the authors and peer reviewers for their valuable contributions to this Special Issue.